2017
DOI: 10.1002/ir.20192
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Models of Student Veteran College Experiences

Abstract: Increases in the student veteran population on college campuses since 2005 spurred a new era of scholarly activity and research on this population. The first wave of studies drew important initial attention to veterans while demonstrating that the field needs more salient conceptual models to understand and study the student veteran experience more holistically and evolve from concepts that only address transitions from the military to higher education (Hammond, 2015;Vacchi & Berger, 2014). A new wave of stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…The stigmatization of disability often follows veterans as they transition to civilian life (Rudstam et al, 2012), and into higher education. Given that there is a growing body of scholarly literature pertaining to student veterans (Albright, Fletcher, Pelts, & Taliaferro, 2017;Pelts & Albright, 2015;Vacchi, Hammond, & Diamond, 2017), there exist opportunities to expand literature pertaining to the discussion of student veterans and invisible disabilities (Gerber, 2001;Jones, 2017). Because many veterans experience invisible disabilities such as PTSD, anxiety, depression, and other mental health issues, there is a need to better understand student veterans within the context of invisible disabilities and stigma.…”
mentioning
confidence: 99%
“…The stigmatization of disability often follows veterans as they transition to civilian life (Rudstam et al, 2012), and into higher education. Given that there is a growing body of scholarly literature pertaining to student veterans (Albright, Fletcher, Pelts, & Taliaferro, 2017;Pelts & Albright, 2015;Vacchi, Hammond, & Diamond, 2017), there exist opportunities to expand literature pertaining to the discussion of student veterans and invisible disabilities (Gerber, 2001;Jones, 2017). Because many veterans experience invisible disabilities such as PTSD, anxiety, depression, and other mental health issues, there is a need to better understand student veterans within the context of invisible disabilities and stigma.…”
mentioning
confidence: 99%
“…After-effects of deployment like physical health concerns (Elliott, 2014), feelings of isolation, and trouble acclimating to a campus (Griffin & Gilbert, 2015) can affect relationships on campus. Serious or unpleasant events during active duty may result in hardened personalities that do not mesh with the attitudes and values of peers (Jones, 2013;Vacchi et al, 2017). Support from faculty may help to mitigate some of the difficulties student veterans face with their undergraduate peers in higher education.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this act of blending in only serves as a temporary fix and does not enhance social integration. Vacchi et al (2017) found that veterans felt more comfortable in the presence of other veterans, providing support and encouragement they were used to. Notwithstanding the differences in age, maturity level, and experience, the relationships with peers are crucial to earning a higher education degree (Gilardi & Guglielmetti, 2011).…”
Section: Peer Relationships With Student Veteransmentioning
confidence: 98%
See 2 more Smart Citations